Mitral valve surgery in a patient 50 years after a pneumonectomy - Oehsen, Hartwig von; Högerle, Benjamin A. (The thoracic and cardiovascular surgeon reports, 2019)
Patients who survive long after pneumonectomy may develop heart valve disease. The consecutive operations can be complex because of the challenging anatomical conditions and the limited physiologic reserves of the patient. Case Presentation The subject is a 78-year-old patient who underwent a left-sided pneumonectomy for a metastasized testicular tumor 50 years ago. At 32 and 37 years postpneumonectomy, mitral regurgitation was manifested, and valve repair was performed. Bioprosthetic mitral valve replacement and tricuspid valve reconstruction became necessary 44 years postpneumonectomy. The patient was fully recovered. Conclusion In case of relevant heart valve disease after pneumonectomies, heart valve surgeries are feasible.